Understanding Brand Loyalty: The Impact of Brand Reputation, Corporate Reputation, and Brand Experience with Mediating Satisfaction on Skincare Facetology - Dilla Nur Rahma; Moechammad Nasir (Lembaga Penelitian Universitas YARSI, 2024)
The purpose of this study is to examine how Facetology Skincare's brand satisfaction mediate the relationship between brand loyalty and company reputation, brand experience, and brand reputation. This study's methodology is quantitative in nature. The participant in this research were students of Muhammadiyah University of Surakarta who use Facetology skincare products. The sampling method employed in this research was non-probability, utilizing a purposive sampling technique. This study compiled its data by utilizing primary data. There were two hundred respondents in this survey. The Likert scale format was employed in the questionnaire's design, and the interval scale is frequently used while creating questions. With the aid of SMARTPLS 3.0 software, PLS (Partial Least Square) was the data analysis method employed in this investigation. The Inner model and the Outer model are the two components of PLS-SEM analysis. The study's findings demonstrated that, for Facetology Skincare, brand satisfaction mediate the relationship between brand loyalty and company reputation, brand reputation, and brand experience. The study's managerial implications offer Facetology strategic direction for boosting brand loyalty through brand and corporate reputation management and consumer experience.